Knowledge, attitude, and practices of beta thalassemia: a cross-sectional study among young adults in Delhi-NCR, India - Oishi Choudhury; Akansha Dubey; Kallur Nava Saraswathy; Roumi Deb; Ravi Ranjan; J. S. Arora; Benrithung Murry; Ram Prasad Mitra; Naorem Kiranmala Devi (BMC Public Health)
Abstract Background Thalassemia is one of the most common monogenic blood disorders worldwide and has a considerable public health burden on India, with a 3.74% prevalence of beta-thalassemia trait. Most ideally, this genetic disease can be managed by prevention through awareness, screening, and counselling. However, prior to this, a background of knowledge, attitude, and practice (KAP) of thalassemia among the population is necessary, which will determine the efficiency of the management programs. Given the paucity of KAP studies in India, the present study aims to report the KAP towards thalassemia among the young adults of Delhi, India. Methods This a cross-sectional study conducted among 1585 adults aged 18–35 years. The socio-demographic and KAP data were collected using a pretested and modified interview schedule. Results Only 36.8% of individuals in the study had ever heard of the term “thalassemia”. Awareness (about the term) was higher among females, Muslims, individuals with higher education, those belonging to upper socio-economic stratum, and Western India, compared to their respective counterparts. In contrast, individuals from schedule caste and other backward classes exhibited lower awareness levels compared to those from unreserved category. A low percentage of 7.7% had adequate knowledge about thalassemia, and education, region, and socio-economic status were its predictors. Overall, 86.7% and 22.6% of sample exhibited positive attitude and practices, respectively. Knowledge was a significant predictor of positive practices; however, negative attitude prevailed despite the adequacy of knowledge. Overall, males exhibited higher odds of negative attitude, and lower education seemed to be an important predictor of both negative attitude and poor/ negative practices. Conclusions The study highlights the need for targeted awareness campaigns among young adults aimed at encouraging positive attitude, practices, and mitigation of associated stigma. College healthcare programs, compulsory inclusion of thalassemia in all high school or college curriculums, and community outreach programs can be effective measures in promoting awareness, thereby enabling the youth to make informed reproductive planning. This can further lay the groundwork for effective implementation of universal screening programs, subsequently contributing towards reduced burden of beta-thalassemia.